Oxidative Stress in Dairy Cows: Insights into the Mechanistic Mode of Actions and Mitigating Strategies - Aurele Gnetegha Ayemele; Mekonnen Tilahun; Sun Lingling; Samy Abdelaziz Elsaadawy; Zitai Guo; Gaojuan Zhao; Jianchu Xu; Dengpan Bu (MDPI AG, 2021)
This review examines several molecular mechanisms underpinning oxidative stress in ruminants and their effects on blood and milk oxidative traits. We also investigate strategies to alleviate or repair oxidative damages by improving animal immune functions using novel feed additives. Microbial pathogenic cells, feeding management, and body condition score were some of the studied factors, inducing oxidative stress in ruminants. The predominance of Streptococcus spp. (24.22%), Acinetobacter spp. (21.37%), Romboutsia spp. (4.99%), Turicibacter spp., (2.64%), Stenotrophomonas spp. (2.33%), and Enterococcus spp. (1.86%) was found in the microbiome of mastitis cows with a decrease of d-mannose and increase of xanthine:guanine ratio when Streptococcus increased. Diversity of energy sources favoring the growth of Fusobacterium make it a keystone taxon contributing to metritis. Ruminal volatile fatty acids rose with high-concentrate diets that decreased the ruminal pH, causing a lysis of rumen microbes and release of endotoxins. Moreover, lipopolysaccharide (LPS) concentration, malondialdehyde (MDA), and superoxide dismutase (SOD) activities increased in high concentrate cows accompanied by a reduction of total antioxidant capacity (T-AOC), glutathione peroxidase (GPx), and catalase (CAT) activity. In addition, albumin and paraoxonase concentrations were inversely related to oxidative stress and contributed to the protection of low-density and high-density lipoproteins against lipid peroxidation, protein carbonyl, and lactoperoxidase. High concentrate diets increased the expression of MAPK pro-inflammatory genes and decreased the expression of antioxidant genes and proteins in mammary epithelial tissues. The expression levels of NrF2, NQO1, MT1E, UGT1A1, MGST3, and MT1A were downregulated, whereas NF-kB was upregulated with a high-grain or high concentrate diet. Amino-acids, vitamins, trace elements, and plant extracts have shown promising results through enhancing immune functions and repairing damaged cells exposed to oxidative stress. Further studies comparing the long-term effect of synthetic feed additives and natural plant additives on animal health and physiology remain to be investigated.